Extension of dynamic source routing protocol in mobile ad hoc network - Ghazali, Osman; Hassan, Suhaidi; Ali, Naseer; Harun, Nur Ziadah; Eh Song, Saichai; Abdullah, Norhidayah (2009)
In a large dynamic network, data can be copied anywhere to make it fault tolerant and easy accessed but there must be an efficient protocol to manage the replicas and make sure the data is consistent and high in availability with a low communication cost. In this paper, we introduced a new protocol, named Diagonal Replication in Mesh (DRM) for data replica control protocol for a large dynamic network by using quorum and voting techniques to improve the availability and the communication cost because quorum techniques reduce the number of copies involved in reading or writing data.The protocol of DRM replicates data for large dynamic network by putting the protocol in a logical mesh structure and access consistent data by ensuring the quorum not to have a nonempty intersection quorum.To evaluate our protocol, we developed a simulation model in Java.Our results proved that DRM improves the performance of the response time compare to Three Dimensional Grid structure Protocol (TDGS).